M. argentina sampling locations, number of individuals (Nind.), voucher, phenological status of individuals of each locality in February (PS): flowering/fruiting, not flowering (—), biogeographic province, geographic coordinates, and haplotypes detected - Amarilla, Leonardo (2015)
Fil: Amarilla, Leonardo D. Universidad Nacional de Córdoba. Facultad de Ciencias Exactas, Físicas y Naturales; Argentina.